Efek Variasi Kandungan Air Terhadap Kerja Gas Engine Cooler Suatu PLTB Limbah Organik Pasar Induk PLTB Limbah Organik Pasar Induk - Dede Hanafi Fajrin; Nazaruddin Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
Organic waste from wholesale market can be degraded to biogas by anaerobic digestion. In PLTB, biogas which has main composition of methane is used as fuel for gas engine to generate electricity. Before being used in the gas engine, biogas is purified and condensed to remove impurity gases. Biogas purification process used a high pressure water scrubber while for condensation used a gas engine cooler. The working of cooler is removing saturated water vapour before gas being burned into gas engine. The purpose of this research is analyzing the effect of water content to the working of cooler for removing water vapour in biogas. To analyze the working of cooler, mass flow of water for anaerobic digestion and water for scrubbing process is varied and simulated by the software AspenPlus V 8.6. In this simulation result, water influences to remove the impurity gases including water vapour. When the input of water is greater in feedstream or make up water, cooler removes water vapour is getting smaller because water vapour dissolved in the water is more.